(untitled) (Herald of Journalism, 2018)
The concept of the national program «Ruhany zhangyru» consists in access to world reserves of science and technology, access to the treasures of world culture, preserving the values of ancestors. A special role in the implementation of this idea belongs to the media, including regional ones. In the article publications about the process through idea of spiritual modernization in mass-media: give the public a broad discussion, explanation. Mobilize the efforts of our journalists in the field of high-quality and impartial information dissemination on the basis of renewed ideology and the promotion of progressive, constructive ideas for the modernization of public consciousness.